Structure and activation of the TSH receptor transmembrane domain - Núñez Miguel, Ricardo; Sanders, Jane; Furmaniak, Jadwiga; Smith, Bernard Rees (Autoimmunity highlights, 2017)
Purpose The thyroid-stimulating hormone receptor (TSHR) is the target autoantigen for TSHR-stimulating autoantibodies in Graves’ disease. The TSHR is composed of: a leucine-rich repeat domain (LRD), a hinge region or cleavage domain (CD) and a transmembrane domain (TMD). The binding arrangements between the TSHR LRD and the thyroid-stimulating autoantibody M22 or TSH have become available from the crystal structure of the TSHR LRD–M22 complex and a comparative model of the TSHR LRD in complex with TSH, respectively. However, the mechanism by which the TMD of the TSHR and the other glycoprotein hormone receptors (GPHRs) becomes activated is unknown. Methods We have generated comparative models of the structures of the inactive (TMD_In) and active (TMD_Ac) conformations of the TSHR, follicle-stimulating hormone receptor (FSHR) and luteinizing hormone receptor (LHR) TMDs. The structures of TMD_Ac and TMD_In were obtained using class A GPCR crystal structures for which fully active and inactive conformations were available. Results Most conserved motifs observed in GPCR TMDs are also observed in the amino acid sequences of GPHR TMDs. Furthermore, most GPCR TMD conserved helix distortions are observed in our models of the structures of GPHR TMDs. Analysis of these structures has allowed us to propose a mechanism for activation of GPHR TMDs. Conclusions Insight into the mechanism of activation of the TSHR by both TSH and TSHR autoantibodies is likely to be useful in the development of new treatments for Graves’ disease.